A Critical Inferno? Hoplit, Hanslick and Liszt’s Dante Symphony - Grimes, Nicole (Journal of the Society for Musicology in Ireland, 2012)
The question of how to distinguish between form with a spiritual dimension and hollow form preoccupied Eduard Hanslick throughout his career as a writer on music aesthetics and as a music critic. His grappling with this issue was not confined to Vom Musikalisch-Schönen. It was manifest in his critical output, where he famously and consistently for many years singled out the music of Liszt as lacking a spiritual dimension. Hanslick has been noted for his views on Liszt since the mid-nineteenth century. More recently, Markus Gärtner has inestimably enhanced our understanding of the nature of the controversy between the two figures. Yet, although we now have a greater understanding of what Hanslick found deplorable in Liszt’s music, we are no closer to understanding why he considered it to lack a spiritual dimension. In other words: Hanslick represents the true dilemma of the critic in this area in that he interprets a lack of spiritual dimension but cannot quantify it. Excerpts of Richard Pohl’s extended essay on Liszt’s Dante Symphony, originally written in 1858, were included in the programme note Hanslick received at the Vienna Philharmonic’s performance of that work in 1881. These passages brought together in Hanslick’s mind the issues and controversies of the 1850s. Drawing both on Pohl’s essay and Hanslick’s review, this article explores what the lasting issues were in Hanslick’s critical reception of Liszt. It further questions what can be meaningfully said in relation to the spiritual dimension of a work, and the nature of Hanslick’s ontological enquiry.